Three new species of Magnolia (Magnoliaceae) endemic to the north-wet-arc in the Maya Highlands of Guatemala - Vázquez-García, J. Antonio; Tribouillier-Navas, Erick; Archila, Fredy; Véliz, Mario; Peña, A. Salome Ortega; Shalisko, Viacheslav (Phytotaxa, 2021)
Three new Magnolia species and a new record from Guatemala are described and illustrated. Two of the new species, M. javieri and M. oscarrodrigoi, are from Alta Verapaz Department and one, M. veliziana, is from Quiché Department. Additionally, M. faustinomirandae is newly reported for the flora of Guatemala. With this contribution, the number of native Guatemalan species increases from 11 to 15 species. An updated distribution map and a key to species are provided. Guatemala, particularly the north-wet-arc in the Maya Highlands, is now an important centre of diversification and endemism for Magnolia. The conservation status of the newly proposed species was unofficially assessed using IUCN criteria.